2015
DOI: 10.1177/1527154415583124
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Sexual Exploitation of Children and State Child Welfare Systems

Abstract: In several states, commercial sexual exploitation of children (CSEC) is now a reportable child abuse offense. Illinois has taken the lead in tackling the issue and the Illinois experience illuminates valuable lessons. This article delineates the protection, practice, and policy implications that evolve when CSEC falls under a state child welfare system. The specific aims are to (a) discuss CSEC, its victims, risks, harms, and challenges inherent in providing effective care; (b) use Illinois as an exemplar to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…In the US, for example, at-risk youth include those who have been sexually abused; youth who lack stable housing; sexual and gender minority youth; youth who have used or abused drugs and/or alcohol; and youth who have experienced homelessness, foster care placement, or juvenile justice involvement [1]. Trafficked children, adolescents, and adults experience adverse social, legal, and health consequences [1][2][3][4][9][10][11][12][13][14][15]. Health consequences are both physical-sexual and reproductive health problems, injuries from physical abuse, and chronic medical conditions-and mental-posttraumatic stress disorder (PTSD), anxiety disorders, depression, substance use, suicidal ideation and attempts, and homicide risk [14].…”
Section: Human Trafficking and Strategies For Its Preventionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the US, for example, at-risk youth include those who have been sexually abused; youth who lack stable housing; sexual and gender minority youth; youth who have used or abused drugs and/or alcohol; and youth who have experienced homelessness, foster care placement, or juvenile justice involvement [1]. Trafficked children, adolescents, and adults experience adverse social, legal, and health consequences [1][2][3][4][9][10][11][12][13][14][15]. Health consequences are both physical-sexual and reproductive health problems, injuries from physical abuse, and chronic medical conditions-and mental-posttraumatic stress disorder (PTSD), anxiety disorders, depression, substance use, suicidal ideation and attempts, and homicide risk [14].…”
Section: Human Trafficking and Strategies For Its Preventionmentioning
confidence: 99%
“…Moreover, both studies identified Illinois as a state whose updated child abuse reporting law requires reporting of both sex and labor trafficking to the state child welfare agency, and a recent report analyzing this law's implications for child protection policy and practice found that the state's child welfare agency was encountering significant obstacles in implementing the updated reporting law [12]. Implementation challenges included the need to build capacity to identify, track, and respond to trafficked children; limitations in the scope of the state's child abuse reporting law to cover only abuse by guardians and caretakers; and conflicting agency policies and priorities [12].…”
Section: Incorporating Trafficking Into Mandatory Child Abuse Reportimentioning
confidence: 99%
See 3 more Smart Citations